Feasibility and acceptability of study methods and psychosocial interventions for body image targeting women diagnosed with breast cancer: a protocol for a systematic review - Aurelie Baillot; Jennifer Brunet; Jenson Price (BMJ Open)
Introduction Improving body image may help to enhance the quality of life of women diagnosed with breast cancer. Although evidence suggests psychosocial interventions can effectively improve body image in this population, no review to date has assessed their feasibility or acceptability. This manuscript reports the protocol for a review summarising current evidence for the feasibility and acceptability of psychosocial interventions for body image targeting women diagnosed with breast cancer and the study methods used to evaluate the interventions in question to provide recommendations to optimise the success and sustainability of psychosocial interventions for body image and future studies. Results will also help to identify gaps in the existing evidence to provide direction for future research.Methods and analysis We searched the following databases for articles published in the English language from January 2000 to June 2021 using a systematic search strategy: MEDLINE, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, PsychINFO and EMBASE. This search will be supplemented with a manual search of reference lists from relevant systematic reviews and included articles. Eligible studies will include peer-reviewed publications reporting on feasibility and acceptability in the evaluation of psychosocial interventions for body image targeting women diagnosed with breast cancer. All study designs are eligible, although articles are required to have reported on an intervention evaluation. Two reviewers will independently carry out study selection, extraction of quantitative and qualitative data and quality assessment. Data will be summarised in a narrative review and thematic analysis.Ethics and dissemination No ethical approval is required because this is a protocol for a systematic review. On completion, results will be submitted for publication in a peer-reviewed scientific journal and for presentation at a relevant conference.Trial registration This protocol has been registered in the Prospective Register of Systematic Reviews international registry (ID: CRD42021269062, 11 September 2021).